TEACHING GRAMMAR - Raimberdiyeva Sabina Elyor qizi; Gaziyeva Saida Turgunovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT           Teaching grammar is a crucial part of language education. Grammar provides the  rules  and  structure  that  govern  language  usage,  allowing  learners  to  construct meaningful  sentences  and  convey  precise  messages.  This  article  explores  the importance of grammar instruction in the classroom, the various methods used to teach grammar,  and  the  challenges  faced  by  both  teachers  and  students.  The  study  also emphasizes the need to balance explicit instruction with communicative practice to ensure grammar becomes an integral part of language proficiency.